Congenital myasthenic syndrome in China: genetic and myopathological characterization. Issue 4 (23rd March 2021) - Zhao, Yawen; Li, Ying; Bian, Yang; Yao, Sheng; Liu, Penju; Yu, Meng; Zhang, Wei; Wang, Zhaoxia; Yuan, Yun
Abstract: Objective: We aimed to summarize the clinical, genetic, and myopathological features of a cohort of Chinese patients with congenital myasthenic syndrome, and follow up on therapeutic outcomes. Methods: The clinical spectrum, mutational frequency of genes, and pathological diagnostic clues of various subtypes of patients with congenital myasthenic syndrome were summarized. Therapeutic effects were followed up. Results: Thirty‐five patients from 29 families were recruited. Ten genes were identified: GFPT1 (27.6%), AGRN (17.2%), CHRNE (17.2%), COLQ (13.8%), GMPPB (6.9%), CHAT, CHRNA1, DOK7, COG7, and SLC25A1 (3.4% each, respectively). Sole limb‐girdle weakness was found in patients with AGRN (1/8) and GFPT1 (7/8) mutations, whereas distal weakness was all observed in patients with AGRN (6/8) mutations. Tubular aggregates were only found in patients with GFPT1 mutations (5/6). The patients with GMPPB mutations (2/2) had decreased alpha‐dystroglycan. Acetylcholinesterase inhibitor therapy resulted in no response or worsened symptoms in patients with COLQ mutations, a diverse response in patients with AGRN mutations, and a good response in patients with other subtypes. Albuterol therapy was effective or harmless in most subtypes. Therapy effects became attenuated with long‐term use in patients with COLQ or AGRN mutations. Interpretation: The genetic distribution of congenital myasthenic syndrome in China is distinct from that of other ethnic origins. The appearance of distal weakness, selective limb‐girdle myasthenic syndrome, tubular aggregates, and decreased alpha‐dystroglycan were indicative of the specific subtypes. Based on the follow‐up findings, we suggest cautious evaluation of the long‐term efficacy of therapeutic agents in congenital myasthenic syndrome.